2018
DOI: 10.1016/j.livsci.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of good practices of handling training on beef cattle welfare and stockpeople attitudes and behaviors

Abstract: The aims of this study were to evaluate the potential impacts of training in good practices of cattle handling on stockpeople's attitudes and behavior, and on cattle welfare, in Brazilian beef farms. Additionally, we aimed to investigate whether the quality of cattle handling deteriorates as the working day progresses. The study was conducted on 24 commercial beef cattle farms (located in Northeastern Pará State, Brazil), which were classified into three groups with different levels of training: Regularly trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 29 publications
3
37
0
6
Order By: Relevance
“…Poorly designed and poorly managed buildings lead to many welfare problems [85]. The training of stockpeople has been shown to substantially improve animal handling on farms, because it helps them understand the behavior of farm animals, positively modifies their attitudes, and improves their conduct toward animals [87][88][89].…”
Section: Welfare Problems Due To Animal Grouping and Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Poorly designed and poorly managed buildings lead to many welfare problems [85]. The training of stockpeople has been shown to substantially improve animal handling on farms, because it helps them understand the behavior of farm animals, positively modifies their attitudes, and improves their conduct toward animals [87][88][89].…”
Section: Welfare Problems Due To Animal Grouping and Handlingmentioning
confidence: 99%
“…Once captured, the animal can be immobilized, if necessary. This immobilization requires adequate equipment, specialized races and other structures, established protocols, and experienced handling by the person handling the animal [89]. Poor quality capture and immobilization generates risks for both the animal and the person who is handling it.…”
Section: Welfare Problems Due To Animal Grouping and Handlingmentioning
confidence: 99%
“…This study shows that the use of electrical shocks produced negative reactions in the animals that were difficult to reverse like slips, jumps, vocalization, and falls. This suggests that handlers need to be trained to better handling natural animal behavior, have a rigorous selection process for personnel, give incentives to those personnel that handle the animals correctly, implement cognitive/behavioral interventions (like handling skills training) and limit the use of electric goads [ 31 ]. Colombian legislation prohibits the use of blunt, sharp, or electric instruments for handling cattle on farms Resolution 2341 of 2007, but does not specify these same conditions in abattoirs [ 20 ], which is why electric goads are used for handling cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have suggested that the reaction of cows in pre-slaughter can be influenced by being in an unfamiliar environment, social separation, and the capacity to perceive stress among animals from the same group [ 19 ]. It is possible that the low aggressive reactivity of the cows in this study to the handling of the personnel is associated with a high level of human acceptance due to dairy systems requiring close contact every day [ 31 ]. In the same way cull cows displayed a predominant behavior of freezing in the face of negative human interactions; this is considered a fear response from cull dairy cows, making them more fearful and difficult to handle [ 33 ], which is the reason why we propose that aggressive handling is unnecessary and that the attitude of personnel towards the animals can be modified to favor a more positive work environment and job satisfaction; this can be done by reinforcing good handling practices and encouraging positive attitudes among the personnel towards the animals.…”
Section: Discussionmentioning
confidence: 99%
“…En un hato establecido, existe relaciones de dominancia sumisión bien establecidas, que permiten la coexistencia de los animales (15) , por lo que cuando se les fuerza a interactuar con otros animales, incrementando su densidad y creando nuevos grupos de diferente rango de edad y peso, estos son factores clasificados como estresores bilógicos (16) . Así mismo, estas prácticas se relacionan con una mala calidad en el manejo del ganado y se asocian con una mayor reactividad, más comportamientos indeseables y un mayor riesgo de accidentes (17,18) . En suma toda situación que rompa con la organización social en una población animal puede desencadenar diferentes grados de estrés (14,19) , esta situación fue propiciada en el presente estudio al provocar un cambio en el entorno espacial durante el llenado de la manga de manejo.…”
Section: Regresarunclassified